Qualidade das informações publicadas em redes sociais sobre controle nutricional do Diabetes Mellitus tipo 2 - Monteiro, Pamela Ione Alves (2025)
The way individuals access and interact with health-related content online has evolved over time. In this context, social media platforms have become popular sources for disseminating information, particularly regarding the management of noncommunicable chronic diseases (NCDs), such as type 2 diabetes mellitus (T2DM). However, the quality of information shared on these platforms raises concerns, given the potential risks of inaccurate guidance that may hinder health education and evidence-based decision-making. This dissertation aimed to systematically evaluate the quality of T2DM-related videos published on Facebook®, Instagram®, and YouTube® through two studies. In the first study, 381 videos were selected using the keyword “type 2 diabetes” and assessed by two independent reviewers using the DISCERN, MQ-VET, and PEMAT-A/V instruments. Regression models were applied to identify predictors of quality, considering video duration, producer profile, and engagement metrics. Overall, the findings revealed that video quality was low to moderate, and video duration was a significant predictor of higher quality across all platforms. Additionally, a disconnect was observed between user engagement (likes, views, and comments) and the quality of the information provided. The second study evaluated 92 videos for compliance with the nutritional recommendations of the Standards of Care in Diabetes—2024 published by the American Diabetes Association (ADA). Videos were selected based on strict eligibility criteria, and a specialized evaluator assessed each item for adherence to the guideline, generating a compliance index ranging from 0 to 1. The overall mean score was 0.4540, indicating low adherence, with no significant differences between platforms or producer profiles. Several videos addressed topics not covered by the ADA guideline, making them ineligible for evaluation. The findings indicate that despite the broad dissemination and potential impact of social media in health education, the quality and reliability of nutritional information about T2DM on these platforms remain limited and may pose risks to users. These results underscore the need for health education strategies that empower individuals to identify trustworthy, evidence-based sources of information on social media, as well as the importance of enhancing regulatory policies to improve access to scientifically grounded content.